The characteristics of the winter durum wheat varieties according to grain quality and pasta properties - N. S. Kravchenko; N. E. Samofalova; I. M. Oldyreva; T. S. Makarova (Зерновое хозяйство России, 2020)
The current paper has presented the study results of grain quality and pasta properties of the new and promising winter durum wheat varieties developed in the FSBSI “Agricultural Research Center “Donskoy” in 2016–2018. The purpose of the study was to evaluate winter durum wheat varieties according to such traits as grain quality and pasta properties to identify the best genotypes and recommend them for use in the breeding process and wider introduction into production. There have been identified the varieties “Yubilyarka” (96%), “Kristella” (94%), “Lakomka” (92%), “Diona” and “Yantarina” (91%) with maximum values of general hardness. All studied genotypes have formed the nature weight of grain corresponding to a first quality class (from 786–814 g/l). There have been identified the varieties “Kristella” (13.9%), “Donchanka” (13.8%), “Diona” (14.0%), “Yakhont” (14.0%), “Yubilyarka” (13.6%), “Yantarina” (13.7%), “Uslada” (13.6%), “Zoloto Dona” (13.6%), “Solntsedar” (13.9%) and “Almaz Dona” (13.5%) with protein percentage in grain corresponding to a first quality class. As a result of the study, it was found that all the studied varieties had good rheological properties of gluten and formed a DCI from 80 units (the variety “Eyrena”) to 102 units (the variety “Donchanka”) and belonged to the 2-nd group. The varieties “Diona”, “Eyrena”, “Yakhont”, “Yantarina” and “Solntsedar” had high rheological properties of dough. There have been identified the genotypes of the varieties “Donchanka” (613 μg/%), “Solntsedar” (626 μg/%) and “Almaz Dona” (630 μg/%) with the maximum concentration of carotenoid pigments, which could be used as sources to improve the trait “carotenoid content”. Throughout the years of study, the varieties were characterized by high indices of dry pasta color (4–5 points). According to a brittle strength of dry pasta there have been identified the varieties “Kristella” (775 g), “Donchanka” (774 g), “Diona” (757 g), “Yantarina” (782 g), “Solntsedar” (766 g) and “Dinas” (769 g) with the best indices of the trait. The varieties identified both by a single and by a set of traits characterizing grain quality of winter durum wheat and its final products, can be used in the breeding process as an adaptive initial material. The introduction of the best varieties into production will partly solve the problem of deficiency of high-quality durum wheat in the south of Russia.